2016
DOI: 10.1134/s1990341316020012
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-flat galaxies selected from RFGC catalog. II. Orbital estimates of halo masses

Abstract: We used the Revised Flat Galaxy Catalog (RFGC) to select 817 ultra-flat (UF) edge-on disk galaxies with blue and red apparent axial ratios of (a/b) B > 10.0 and (a/b) R > 8.5. The sample covering the whole sky, except the Milky Way zone, contains 490 UF galaxies with measured radial velocities. Our inspection of the neighboring galaxies around them revealed only 30 companions with radial velocity difference of | ∆V |< 500 km s −1 inside the projected separation of R p < 250 kpc. Wherein, the wider area around … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…(1) the number of the galaxy in the RFGC catalog; (2) the equatorial coordinates; (3,4) the "blue" angular diameter in arcmin and apparent "blue" axial ratio from RFGC; (5) the heliocentric radial velocity of the galaxy in km s −1 ; (6) the effective wavelength of the filter ( Å) in which the galaxy was exposed; (7)…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…(1) the number of the galaxy in the RFGC catalog; (2) the equatorial coordinates; (3,4) the "blue" angular diameter in arcmin and apparent "blue" axial ratio from RFGC; (5) the heliocentric radial velocity of the galaxy in km s −1 ; (6) the effective wavelength of the filter ( Å) in which the galaxy was exposed; (7)…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Firstly, they are distributed over the sky quite homogeneously, without any visible clumps in the areas occupied by clusters of galaxies [28]. A more detailed examination has shown that about 60% of ultra-flat edge-on galaxies are isolated, while about 30% belong to diffuse associations of galaxies, and only 10% have nearby, physically bound neighbors [30,31]. It can therefore be assumed that star formation in these objects is mainly due to the internal processes, not being affected by nearby neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…or sSFR(M*) relationships. The important feature of these galaxies is their localization in regions of low cosmic density [8], where there are no noticeable traces of interactions with nearby neighbors.…”
Section: Introductionmentioning
confidence: 99%